Application of the Jigsaw Puzzle Flap Based on Freestyle Perforators to Repair Large and Deep Ulcers on the Buttocks - Chen, Xiaoming; Huang, Biao; Xiao, Haitao; An, Lu; Su, Wenxing; Yu, Daojiang (Frontiers in Surgery, 2022)
Abstract Background: Decubitus ulcers are common skin injuries in plastic and burn surgery departments, usually occur in patients with a long disease course and poor underlying health. Designing a reconstruction procedure with safety blood supply to a large volume soft tissue and resulting in minimal trauma is a priority for surgeons. Methods: The free-style perforators on the potential donor sites surrounding the ulcers were detected by Doppler, and the area of the ulcer was divided into several sections based on the location of pre-design perforator flaps. According to the insertion point of the perforators, small V-Y advancement flaps, propeller flaps and rotation flaps pedicled with freestyle perforators were formed and moderately modified during surgery. All of the small flaps were transplanted from donor sites to the defect and reassembled into a new composite flap to repair the ulcer. The donor sites were directly closed. The area of the flaps ranged from 7.0 cm × 10.5 cm to 8.0 cm × 22.0 cm and the diameter of the pedicle perforators ranged from 0.5 mm to 4.0 mm. Results: In 30 patients, 65 flaps were constructed, and all of the flaps survived with direct closure of all donor sites. One case with effusion healed 1 month postoperatively through draining and application of a mild pressure dressing. After a 3–24 months follow-up period, all of the patients were satisfied with post-operative function and appearance, and only one case had a local recurrence 6 months postoperatively. Conclusion: The jigsaw puzzle flap based on freestyle perforators can repair the large skin and soft tissue defects caused by decubitus ulcers on the buttocks, with direct donor flap area closure. This method is easy to perform with a safe blood supply and minimal trauma resulting from the avoidance of microvascular anastomosis and the conventional myocutaneous flap.